M. Eitingon correspondence - Eitingon, M. (Max), 1880-1943.
ALS (1914 July 14) from Eitingon to Maria Gurewitsch-Markowitsch regarding a book.
Psychoanalyst.
In German.
Forms part of: Sigmund Freud collection.
Keywords: Gurewitsch-Markowitsch, Maria -- Correspondence; Psychoanalysts